Universal Free School Meal Programs in Vermont Show Multi-domain Benefits. Issue 6 (1st November 2020) - Taylor, Josiah; Garnett, Bernice; Horton, M. Anore; Farineau, Ginger
ABSTRACT: Background : School meals help combat consequences of poverty for child development. Universal school meal programs provide all children free meals regardless of income; outcomes are under-studied. Methods : This paper analyzes the impacts of universal school meals on multiple domains of child development, including schools' social climates, student academics and behavior, family–school relationships, and school finances. In total, 240 staff at 57 K-12 universal meal schools in Vermont were surveyed in 2017. Results : Universal meals yield positive results for Vermont children and schools. Policymakers and researchers will find this data relevant, as it represents an early statewide study of K-12 universal meal programs.